Pengaruh Kualitas Produk, Kualitas Layanan Dan Citra Perusahaan Terhadap Kepuasan Konsumen Pada UMKM Dapur Keyra Kec. Puri Kab. Mojokerto - Muhammad Al Zidane; Imam Baidlowi; Agoes Hadi Purnomo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
In Indonesia, more and more individuals are doing business activities. Business is an activity carried out by one individual. Micro, Small and Medium Enterprises (MSMEs) are businesses engaged in trade, which involve entrepreneurial activities. UMKM Kitchen Keyra is one of the businesses engaged in the field of food that is easy to develop, which is located on Jalan Kebonagung Village, Kec. Kab. Castle Mojokerto. The purpose of this study was to determine the effect of product quality on customer satisfaction, to determine the effect of service quality on customer satisfaction, to determine the effect of corporate image on customer satisfaction and to determine the effect of product quality, service quality and corporate image on customer satisfaction. This study uses quantitative methods, with a sample of 100 respondents with the help of IBM SPSS version 25. The results show that product quality variable (X1) partially and significantly influences consumer satisfaction (Y) with t count 7.801 > 1.98498 and a sig value of 0.000 <0.05, service quality (X2) has a partial and significant effect on customer satisfaction (Y) with t count 2.531 > 1.98498 and a sig value of 0.013 <0.05, and corporate image (X3) has a partial and significant effect on consumer satisfaction (Y) with t count 16.567 > 1.98498 and a sig value of 0.000 <0.05, while simultaneously product quality (X1), service quality (X2) and corporate image (X3) have a positive and significant effect on consumer satisfaction ( Y) Keyra Kitchen SMEs with f count 292.834 > 2.70 and a sig value of 0.000 <0.05